2021
DOI: 10.1097/cce.0000000000000529
|View full text |Cite
|
Sign up to set email alerts
|

Explainable Machine Learning on AmsterdamUMCdb for ICU Discharge Decision Support: Uniting Intensivists and Data Scientists

Abstract: Objectives: Unexpected ICU readmission is associated with longer length of stay and increased mortality. To prevent ICU readmission and death after ICU discharge, our team of intensivists and data scientists aimed to use AmsterdamUMCdb to develop an explainable machine learning–based real-time bedside decision support tool. Derivation Cohort: Data from patients admitted to a mixed surgical-medical academic medical center ICU from 2004 to 2016. Validation Coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Lastly, training will be needed to educate physicians on the interpretation of the mortality or readmission risk predictions, as we observed a range of answers regarding the threshold at which patients would or would not be discharged to lower care wards (Figure 3). Due to a significant imbalance in the number of patients that were or were not readmitted or died after discharge, risk predictions are skewed along the 0% to 100% scale, being concentrated around an event rate of 5.3% [25]; the respondents were not informed of this. Therefore, attention should be paid to the interpretation of these calibrated risk predictions during training, as perceptions clearly differed on what constituted high and low risks for this outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, training will be needed to educate physicians on the interpretation of the mortality or readmission risk predictions, as we observed a range of answers regarding the threshold at which patients would or would not be discharged to lower care wards (Figure 3). Due to a significant imbalance in the number of patients that were or were not readmitted or died after discharge, risk predictions are skewed along the 0% to 100% scale, being concentrated around an event rate of 5.3% [25]; the respondents were not informed of this. Therefore, attention should be paid to the interpretation of these calibrated risk predictions during training, as perceptions clearly differed on what constituted high and low risks for this outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This survey study is part of preimplementation research for Pacmed Critical [24]. Pacmed Critical is a machine learning-based AI-CDS tool that predicts a patient's combined readmission and mortality risk within 7 days of ICU discharge to support physicians in their decisions to discharge patients to lower care wards [25,26]. The Pacmed Critical software is intended for use as a complementary tool by qualified ICU medical professionals and will be accessed on hospital premises; it will not be used on mobile devices.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the individual effects of ML techniques are relatively hard to interpret. Although more explainable algorithms exist, effects are less intuitive to interpret than regression coefficients [103]. There are some extensions of ML techniques that allow the researcher to assume relationships between variables, for example, through graph-based neural networks [104] or Bayesian networks [102,105].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of the application of machine learning in predicting hospital readmission identified 43 relevant studies employing a variety of modeling methods (Huang et al, 2021). Additional studies have focused on predicting multiple outcomes simultaneously including both post-discharge mortality and readmission (Badawi and Breslow, 2012;Campbell et al, 2008;Ouanes et al, 2012;Thoral et al, 2021), as well as length of stay and readmission (Hilton et al, 2020).…”
Section: Literature Overviewmentioning
confidence: 99%